Suppression, Maintenance, and Surprise: Neuronal Correlates of Predictive Processing Specialization for Musical Rhythm - Færøvik, Ulvhild; Specht, Karsten; Vikene, Kjetil (Frontiers in Neuroscience, 2021)
Auditory repetition suppression and omission activation are opposite neural phenomena, and manifestations of principles of predictive processing. Repetition suppression describes the temporal decrease in neural activity when a stimulus is constant or repeated in an expected temporal fashion, omission activity is the transient increase in neural activity when a stimulus is temporarily and unexpectedly absent. The temporal, repetitive nature of musical rhythms is ideal for investigating these phenomena. During an fMRI-session , 10 healthy participants underwent scanning while listening to musical rhythms with two levels of metric complexity, and with beat-omissions with different positional complexity. Participants first listened to 16-second long presentations of continuous rhythms, before listening to a longer continuous presentation with beat-omissions quasi-randomly introduced. We found deactivation in bilateral superior temporal gyri during the repeated presentation of the normal, unaltered rhythmic stimulus, with more suppression of activity in the left hemisphere. Omission activation of bilateral middle temporal gyri were right lateralized. Persistent activity was found in areas including SMA, caudate nucleus, anterior insula, frontal areas, and middle and posterior cingulate cortex, not overlapping with either listening, suppression or omission activation. This suggests that the areas are perhaps specialized for working memory maintenance. We found no effect of metric complexity for either the normal presentation or omissions, but we found evidence for a small effect of omission position – at an uncorrected threshold – where omissions in the more metrical salient position, i.e., the first position in the bar, showed higher activation in anterior cingulate / medial superior frontal gyrus, compared to omissions in the less salient position, in line with the role of the anterior cingulate cortex for saliency detection. The results are consistent with findings in our previous studies on Parkinson’s disease, but are put into a bigger theoretical frameset.